Pengaruh Kualitas Makanan dan Kualitas Layanan terhadap Kepuasan Pelanggan Melalui Harga di Waroeng Spesial Sambal (SS) di Tangerang - Sugiyanto; Siti Annisa (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
In the current restaurant competition, many new restaurants are emerging so that restaurant competition is getting tougher. To win the restaurant competition, business actors must be smart in competing. One way to do this is to increase customers and retain them. The aim of this research is to understand how the quality of the food served at Waroeng Special Sambal affects the level of customer satisfaction. Data collection is through questionnaires distributed via Google Form and distributed online. We used SmartPls Structural Equation Modeling (SEM) to test this research model with a sample size of 175 respondents, the sample was selected using the Purposive Sampling method. The results of data processing show the effects, namely food quality has a positive effect on customer satisfaction, price has a positive effect on customer satisfaction, service quality has a positive effect on customer satisfaction, food quality has a positive effect on price, service quality has a positive effect on price, food quality has a positive effect on customer satisfaction which is mediated by price, service quality has a positive effect on customer satisfaction which is mediated by price. Future research is expected to involve more specific respondents and use different measurement techniques. To attract customer satisfaction, restaurants need to improve food quality and service quality and offer prices that match the menu served.